2014
DOI: 10.5389/ksae.2014.56.6.019
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Water Quality and Soil Environment in Paddy Fields Partially Irrigated with Untreated Wastewater

Abstract: The objectives of this study were to monitor and analyse water quality and soil property in paddy fields where untreated wastewater is irrigated. Three paddy fields where streamflow mixed with untreated wastewater has been irrigated (untreated wastewater district, UWD) were selected for monitoring, and five paddy fields in Yongin area (Yongin district, YID) where water from Idong agricultural reservoir (well-managed) has been irrigated were selected for comparative evaluation. Electronic conductivity (EC), sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 24 publications
1
14
0
1
Order By: Relevance
“…Even for sites irrigated by relatively clean water derived from a reservoir, an average of about 15,700 MPN/100 mL of total coliform was detected [20]. It was also found that the total coliform of the irrigation water containing untreated wastewater was about 77,000 MPN/100 mL [21]. QMRA on paddy irrigation showed that the human health risk of irrigating treated wastewater is nine times higher than that of irrigating groundwater [42], but even with the extremely high level of total coliform, there have rarely been any reports of human harm from using treated or untreated wastewater for rice paddy irrigation.…”
Section: Coliform Bacteriamentioning
confidence: 81%
See 3 more Smart Citations
“…Even for sites irrigated by relatively clean water derived from a reservoir, an average of about 15,700 MPN/100 mL of total coliform was detected [20]. It was also found that the total coliform of the irrigation water containing untreated wastewater was about 77,000 MPN/100 mL [21]. QMRA on paddy irrigation showed that the human health risk of irrigating treated wastewater is nine times higher than that of irrigating groundwater [42], but even with the extremely high level of total coliform, there have rarely been any reports of human harm from using treated or untreated wastewater for rice paddy irrigation.…”
Section: Coliform Bacteriamentioning
confidence: 81%
“…This indicates that the subjected level of total coliform can be easily found in nature and is inadequate as an indicator for microbes. The E. coli concentration of irrigation water with high levels of total coliform concentration was measured to be 13, 46, and 107 MPN/100 mL for reservoir water, indirect wastewater reuse water, and irrigation water containing untreated wastewater, respectively [20,21]. For fecal coliform, the concentrations for the subjects above were 5000, 180, and 633 MPN/100 mL, respectively [20,21].…”
Section: Coliform Bacteriamentioning
confidence: 99%
See 2 more Smart Citations
“…(Fig. 1(a)) Song et al, 2014). 이동저수지는 4∼9월에 취수탑을 통해 1,789.7ha 의 면적에 대해 농업용수를 공급하고 있으며, 홍수기에는 농업용수 공급의 지장이 없는 범위 내에서 radial gate를 .…”
unclassified